Solve a system equation

Hi everybody,
Please I want to Solve the system:

3x-2y=19
y3-2x=19

x,y real number!

Thank you !
 PhysOrg.com science news on PhysOrg.com >> New language discovery reveals linguistic insights>> US official: Solar plane to help ground energy use (Update)>> Four microphones, computer algorithm enough to produce 3-D model of simple, convex room
 Mentor I think clever guessing (and showing that there are not other solutions) is the quickest method. You can solve one of those equations for a single variable and put this into the other equation, but I don't think you cannot simply find solutions like that.
 Blog Entries: 9 Recognitions: Homework Help Science Advisor It looks like 3,3 is the only solution.

Mentor

Solve a system equation

There is another solution near y=20.8216, x=13.1370.
 Please I want the steps to find it, because I'm stumbled in the last steps as follow: x*Ln(3)-y*Ln(2)=Ln(19) 3*Ln(y)-x*Ln(2)=Ln(19) x*Ln(3)-y*Ln(2) - 3*Ln(y)-x*Ln(2) = 0 x*Ln(3)+x*Ln(2) = y*Ln(2)+3*Ln(y) {each one equals Ln(19)} x*Ln(3)+x*Ln(2) = y*Ln(2)+3*Ln(y) = Ln(19) x*Ln(6) = y*Ln(2)+3*Ln(y) = Ln(19) x = ln(19)/ln(6) ..... Here I'm stumbled. Thank you for your response.
 Mentor There is no useful way to simplify ln(19)/ln(6). It is just some number - and it is wrong. The first step does not work. ln(a-b) is not the same as ln(a) - ln(b). The third step looks wrong, too (where you say "{each one equals Ln(19)}").

Mentor
 Quote by naoufelabs 3x-2y=19 y3-2x=19 x,y real number!
The first equation below is wrong, so everything below it is also invalid.

You apparently took the natural log of both sides, like so:
ln(3x - 2y) = ln(19)

Then you "distributed" the ln operation like this:
ln(3x) - ln(2y) = ln(19)
This is the step that is incorrect. There is no property of logs in which ln(A + B) = ln(A) + ln(B).

 Quote by naoufelabs Please I want the steps to find it, because I'm stumbled in the last steps as follow: x*Ln(3)-y*Ln(2)=Ln(19) 3*Ln(y)-x*Ln(2)=Ln(19) x*Ln(3)-y*Ln(2) - 3*Ln(y)-x*Ln(2) = 0 x*Ln(3)+x*Ln(2) = y*Ln(2)+3*Ln(y) {each one equals Ln(19)} x*Ln(3)+x*Ln(2) = y*Ln(2)+3*Ln(y) = Ln(19) x*Ln(6) = y*Ln(2)+3*Ln(y) = Ln(19) x = ln(19)/ln(6) ..... Here I'm stumbled. Thank you for your response.
 Thank you all.

 Similar Threads for: Solve a system equation Thread Forum Replies Calculus & Beyond Homework 4 Precalculus Mathematics Homework 5 Linear & Abstract Algebra 2 Precalculus Mathematics Homework 4